Association between physical activity motives and type of physical activity in children. Issue 3 (27th May 2017) - Goguen Carpenter, Julie; Bélanger, Mathieu; O'Loughlin, Jennifer; Xhignesse, Marianne; Ward, Stéphanie; Caissie, Isabelle; Sabiston, Catherine
Abstract : Objectives : Motives for participating in a specific type of physical activity (PA) may differ across PA type in youth. We studied the relationship between PA motives and type of PA engaged in by youth. Design : Cross-sectional analysis using data from the Monitoring Activities of Teenagers to Comprehend their Habits ( MATCH) study. Method : Eight hundred and two students age 10–11 years from 17 primary schools in New Brunswick, Canada completed a questionnaire that collected data on type of PA participated in (individual, group-based, organised and non-organised), PA motives (enjoyment, social affiliation, competence, fitness/health, and appearance) and attainment of PA guidelines (60 minutes of moderate-to-vigorous PA (MVPA) per day). The associations between PA motives and PA type and between PA motives and attainment of PA recommendations were assessed in multi-level logistic regression models. Results : Endorsing enjoyment motives was associated with participation in organised PA (odds ratio, 95% confidence interval (CI): 1.54, 1.24–1.91). Competence motives were associated with participation in group-based PA (1.27, 1.11–1.46) and achievement of PA recommendations (1.95, 1.37–2.78). Conclusion : Targeting enjoyment and competence motives may be associated with increased participation in organised and group-based PA as well as with an increased likelihood of meeting PA guidelines in youth.